Unlocking the potential of Cu3SbSe3: ultralow thermal conductivity and enhanced thermoelectric performance - Saglik, Kivanc (2024)
Cu3SbSe3, with its ultralow thermal conductivity and Earth-abundant elements, has emerged as a promising thermoelectric material. However, synthesizing its pure phase and achieving effective doping have proven to be challenging. In this study, we present our findings on the investigation of thermoelectric properties of stoichiometric and off-stoichiometric Cu3SbSe3 compositions along with various doping strategies. Our results demonstrate that samples with non-stoichiometric compositions and Bi doping further reduces the lattice thermal conductivity of 0.16 W/mK. The consistently moderate Seebeck coefficient leads to a zT value of 0.25 at 650 K across all cation-deficient samples. Furthermore, we observed that 5% Bi doping further enhances the zT value to 0.35, representing a 52% improvement over pristine Cu3SbSe3. We believe that the compositional insensitivity of zT and the enhanced performance achieved through Bi doping offer new opportunities for exploring materials with ultra-low thermal conductivity in the field of thermoelectrics.